ISOLASI DAN KARAKTERISASI SENYAWA ALKALOID DARI BIJI TUMBUHAN SIRSAK (Annona muricata Linn) - Idrus, Rifki Brahmono; Bialangi, Nurhayati; Alio, La (Sainstek, 2013)
Isolation and Characterization of Alkaloid Compounds from Plant Sirsak (Annona muricata Linn.) Seeds. Have done the isolation and characterization of the alkaloid content in seeds of Sirsak (A muricata Linn) plant. Isolation was performed with the maceration extraction by using methanol solvent. Condensed methanol extracts fractionated successively with n-hexane and ethyl acetate. Further separation process that is focused on condensed methanol extract using column chromatography, as used silica gel stationary phase and mobile phase was a mixture of n-hexane: ethyl acetate, and ethyl acetate: methanol with gradient have. Purity of the isolates obtained was tested using Thin Layer Chromatography. Isolates were further characterized using UV-Vis and Infrared. The results of spectroscopic analysis of UV-Vis and Infrared (IR) suggested that isolates is a class of alkaloid compound with Alkaloids-Indole type that have characteristics of functional groups N-H, aliphatic C-H, C-N, C=C aliphatic, C=O, =C-H aromatic and provide wavelength spectra max 282.5 nm and 237.5 nm.